2023
DOI: 10.1021/acsabm.2c00965
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced In Vivo Radiotherapy of Breast Cancer Using Gadolinium Oxide and Gold Hybrid Nanoparticles

Abstract: Radiation therapy has demonstrated promising effectiveness against several types of cancers. X-ray radiation therapy can be made further effective by utilizing nanoparticles of high-atomic-number (high-Z) materials that act as radiosensitizers. Here, in purpose of maximizing the radiation therapy within tumors, bovine serum albumin capped gadolinium oxide and gold nanoparticles (Gd 2 O 3 @BSA-Au NPs) are developed as a bimetallic radiosensitizer. In this study, we incorporate two high-Z-based nanoparticles, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…10 Utilization of nanoradiosensitizers composed of high atomic number elements has been shown to significantly improve cancer therapy efficacy. [11][12][13] Furthermore, chemotherapy or its combination with surgery or radiotherapy can be employed in breast cancer therapy. 14,15 In recent years, immunotherapy approaches such as application of checkpoint inhibitors have been developed for breast cancer treatment and to improve the overall survival of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Utilization of nanoradiosensitizers composed of high atomic number elements has been shown to significantly improve cancer therapy efficacy. [11][12][13] Furthermore, chemotherapy or its combination with surgery or radiotherapy can be employed in breast cancer therapy. 14,15 In recent years, immunotherapy approaches such as application of checkpoint inhibitors have been developed for breast cancer treatment and to improve the overall survival of patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that among 10,801 breast cancer patients who have undergone mass resection, application of radiotherapy significantly improves their survival rate and decreases their 10‐year recurrence rate 10 . Utilization of nanoradiosensitizers composed of high atomic number elements has been shown to significantly improve cancer therapy efficacy 11–13 . Furthermore, chemotherapy or its combination with surgery or radiotherapy can be employed in breast cancer therapy 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) are distinguished from bulk materials by their unique electrochemical, optical, and thermal characteristics, as well as their much larger surface area to volume ratio. Due to their distinctive features, NPs have found broad usage in a variety of scientific areas, including agriculture, biotechnology, chemistry, communications, electronics, energy, material science, medicine, microbiology, optics, and various engineering fields. From metals and their related oxides, NPs have been created using several physical and chemical procedures, including ultrasonication, microwave irradiation, laser vaporization, wet impregnation, and sol–gel approaches. , These synthesis methods intensively use toxic and hazardous substances that harm the environment and require stringent conditions and expensive equipment to operate. , Therefore, the development of proficient, economical, and environmentally friendly green approaches for the synthesis of NPs is of high value. Plant extracts can serve as a viable precursor for the environmentally friendly synthesis of nanomaterials .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, their clinical implementation has not yet been applied. Gd-based NPs, as high atomic number particles, have also been utilized as radiosensitizers [5][6][7]. Due to Gd's inherent toxicity, as part of the lanthanide group, various polymers, such as silica or polyethylenimine (PEI) pre-modified with polyethylene glycol (PEG), were used as coating on hte GdNPs' surfaces [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Gd-based NPs, as high atomic number particles, have also been utilized as radiosensitizers [5][6][7]. Due to Gd's inherent toxicity, as part of the lanthanide group, various polymers, such as silica or polyethylenimine (PEI) pre-modified with polyethylene glycol (PEG), were used as coating on hte GdNPs' surfaces [6,8,9]. Thereinafter, GdNPs have been utilized in MRI-guided radiotherapy, photodynamic and photothermal therapy with near-infrared fluorescence imaging capabilities, and in dual mode magnetic resonance/computed tomography imaging [6,10,11].…”
Section: Introductionmentioning
confidence: 99%